Mechanism of double exposure strategy for improving down-skin roughness and dimensional accuracy in support-free printing - Ting Zhang; Xin zhou; Dianzheng Wang; Zhibin An; Guoquan Ding; Hanyu Gao; Dongliang Bian (Materials & Design)
Laser Powder Bed Fusion (LPBF) additive manufacturing of support-free structures faces key technical challenges regarding down-skin quality and forming accuracy. This study first analyzed the impact of laser input energy on these factors. Subsequently, we proposed a double exposure strategy for the down-skin in support-free forming. Comparative analysis showed that double exposure significantly improved down-skin quality and forming accuracy, with more uniform energy distribution yielding better results. Specifically, down-skin roughness improved by 14.92 % and dimensional accuracy by 30.91 % compared to the best single-exposure specimen. Additionally, simulation analysis revealed the spreading and solidification mechanism of the melt pool in the overhanging region, discussing the formation of down-skin roughness and dimensional errors. This study provides technical guidance for LPBF support-free forming of overhanging structures.